Pengaruh Pendekatan Pembelajaran Kontekstual Terhadap Motivasi Belajar Pendidikan Agama Islam Di Sekolah Dasar - Dety Mulyanti; Rheza Fasya (International Forum of Researchers and Lecturers, 2024)
Learning motivation plays a crucial role in improving students' understanding and engagement with the subject matter. Contextual learning approach is considered as a method that can motivate students by linking learning with the context of their daily lives. This study aims to investigate the effect of contextual learning approach on Islamic Religious Education (PAI) learning motivation in elementary schools. This research uses qualitative research methods with a literature approach, primary and secondary data obtained from studies that have been published in journals that have high credibility sinta 2 and 5, which discuss the effect of contextual learning approaches on learning motivation for Islamic religious education in elementary schools. After the data is collected, data analysis is carried out and the data is grouped according to its type, and finally draws conclusions as expected. The results showed that students who received learning with a contextual approach had a significant increase in learning motivation compared to the control group. In addition, the comprehension score of PAI material also increased significantly in the experimental group. This shows that the contextual learning approach can positively contribute to students' learning motivation and understanding of PAI materials. This research makes an important contribution to the development of PAI learning methods in elementary schools. The practical implication is that PAI teachers can consider the use of contextual learning approach in designing and implementing learning strategies in order to increase students' motivation and understanding of Islamic Religious Education.